2018
DOI: 10.1002/ange.201804298
|View full text |Cite
|
Sign up to set email alerts
|

Stable Boron Dithiolene Radicals

Abstract: Whereas low‐temperature (−78 °C) reaction of the lithium dithiolene radical 1. with boron bromide gives the dibromoboron dithiolene radical 2., the parallel reaction of 1. with (C6H11)2BCl (0 °C) affords the dicyclohexylboron dithiolene radical 3.. Radicals 2. and 3. were characterized by single‐crystal X‐ray diffraction, UV/Vis, and EPR spectroscopy. The nature of these radicals was also probed computationally. Under mild conditions, 3. undergoes unexpected thiourea‐mediated B−C bond activation to give zwitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In Figure 3 , the optimized C–C distances and the corresponding Wiberg bond indices (WBIs) 97 are compared for a variety of R′ 2 timdt derivatives showing a C=C double bond, as in 4,5,9,10-tetrathiocino[1,2- b :5,6- b ′]diimidazolyl-1,3,6,8-tetramethyl-2,7-dithione (Me 2 timdt) 2 and compound 7 , 74 or a single bond, as in the neutral complex 2 and in compound 5 ( Chart S2 ). 72 , 73 For these compounds, a clear correlation ( R 2 = 0.99) holds between the optimized C–C bond distance d C–C within the R 2 timdt ring and the corresponding WBI C–C values. This clearly shows that WBIs calculated at the optimized distances represent a reliable parameter for evaluating the charge distribution and hence the oxidation state of noninnocent 1,2-dithiolene ligands.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In Figure 3 , the optimized C–C distances and the corresponding Wiberg bond indices (WBIs) 97 are compared for a variety of R′ 2 timdt derivatives showing a C=C double bond, as in 4,5,9,10-tetrathiocino[1,2- b :5,6- b ′]diimidazolyl-1,3,6,8-tetramethyl-2,7-dithione (Me 2 timdt) 2 and compound 7 , 74 or a single bond, as in the neutral complex 2 and in compound 5 ( Chart S2 ). 72 , 73 For these compounds, a clear correlation ( R 2 = 0.99) holds between the optimized C–C bond distance d C–C within the R 2 timdt ring and the corresponding WBI C–C values. This clearly shows that WBIs calculated at the optimized distances represent a reliable parameter for evaluating the charge distribution and hence the oxidation state of noninnocent 1,2-dithiolene ligands.…”
Section: Resultsmentioning
confidence: 87%
“…The C–C distance in the Me 2 timdt ligand of 3 (1.454(16) Å) is intermediate between the corresponding distance in [Pd(Et 2 timdt)Br 2 ] (1.474(10) Å; Chart S2 ), 48 featuring an authentic neutral Et 2 timdt ligand, and that of Li( 5 , R″ = 2,6-diisopropylphenyl, Chart S2 ; 1.417(4) Å), featuring the R″ 2 timdt •– radical monoanion. 72 , 73 Analogously, the C(4)–C(4) i distance in 3 (1.364(16) Å) is shorter than that found in [Pd(mnt) 2 ] ( 4 ; 1.39(2) Å; Chart S2 ) 116 and the average value for 4 – monoanions (1.377(24) Å) 117 but slightly larger than the average value found in salts of the complex 4 2– (1.359(19) Å). 118 This suggests that the Me 2 timdt ligand in 3 should be considered to carry a partial negative charge and that the GS of 3 should include a partial DC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1924, the Krause group reported that the reaction of triphenylborane and sodium in diethyl ether resulted in a product with the chemical composition of NaBPh 3 , which was later confirmed to be a radical anion. Since then, the study of boron-containing radical species has received tremendous research interest, which might be ascribed to their applications in chemical sensors, organic synthesis, polymer chemistry, and material science. In the past decades, many boron-containing radical compounds have been successfully designed and synthesized. The synthesis of these radical species has mainly relied on the reduction of organoboron compounds by strong reducing agents, such as Li, Na, K, etc . Generally, stable boron-centered radical compounds can be obtained through the steric effect of the substituents or spin delocalization through π conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…The anionic diisopropylphenyl-substituted N-heterocyclic dicarbene NHDC Dipp (Scheme 2), reported by this laboratory, 27 has proven to be a versatile synthetic platform from which a variety of abnormal carbene-based complexes, poly-NHCs, NHDC-based binuclear complexes, main-group dithiolene radicals, 28,29 and C4-functionalized NHCs may be accessed. 30−34 Notably, our synthetic efforts regarding the lowtemperature reaction of NHDC Dipp with Cp 2 Ti IV Cl 2 in THF and subsequent workup in toluene did not afford the expected C4-titanocenyl-substituted N-heterocyclic carbene.…”
Section: ■ Introductionmentioning
confidence: 99%